ROLE OF OLIVE OIL IN CANCER PREVENTION - Pradnyandari, GAP Ratih; Wiryawan, IGN Sri (E-Jurnal Medika Udayana; vol 3 no 2 (2014):e-jurnal medika udayana)
Cancer is the second leading cause of death in the United States. From this fact shows how ferociously the disease if not treated well. The emergence of this disease is caused by various factors, but often caused by damage to the structure of DNA and other molecular structures by a reactive oxygen species (ROS). Early prevention that can be implemented, is to improve the lifestyle and diet that contains a substance that can protect our body cells from damage caused by ROS. These molecules called antioxidants. Therefore, antioxidants are often called reducing agents (thiol or polyphenols). Olive oil is the one of the exogenous antioxidants have many benefits especially polyphenols that have chemo preventive effects on several types of cancer, and can inhibit the process of carcinogenesis by several mechanisms such as inhibition of DNA synthesis in the process, reducing the production of ROS, regulate cell cycle, regulate proliferation and survival mechanisms of cells.
Keywords: olive oil, antioxidant, cancer prevention